ENFORCEMENT OF MARITIME ARCHAEOLOGY IN MALAYSIA: A REVIEW - Hariry, Nik Nurhalida Binti Nik; Mokhtar, Fahirah Syaliza binti; Mokhtar, Nor Aeini binti Haji; Nordin, Mohd Norazmi bin (The journal of contemporary issues in business and government, 2021)
The development of conservation and law enforcement for underwater cultural heritage in Malaysia has been slow due to some internal problems. Among them are that Malaysia does not have expertise in excavation, lack of funding, insufficient tools and awareness of the importance of underwater cultural heritage is still not sufficiently disseminated. maritime and still employs experts from abroad such as Michael Flecker and Sten Sjostrand. when enlisting the help of the custodians of historic objects from every shipwreck discovery in the world. which has a great influence on the status of maritime archeology, especially in the process of rescuing historical objects in Malaysia. UNESCO Convention 2001 the Convention on the Protection of the Underwater Cultural Heritage is a convention on the protection and preservation of historic underwater objects such as shipframes such as ships, airplanes, any form of vehicle including cargo and cargo